Quality of Life and Daily Travel (Applying Quality of Life Research, Best Practices,, 2018)
This volume analyses the relevance of daily travel in the quality of life of individuals. It provides a broad understanding of the links between life satisfaction, well-being and travel, the importance of commuting, and different evaluations and measures to assess the experience of commuting and quality of life. Chapters in this book relate travel and quality of life to the built environment, accessibility and exclusion, travel mode choice, travel satisfaction and emotions. It brings together distinguished researchers from a variety of academic backgrounds providing conceptualizations and applications, presented as case studies, for daily travel and well-being. Findings presented in this book are highly relevant for transport planners, transport marketers, public transport authorities, and environmental professionals in the pursuit of improving people's life.